Mathematical Foundations of Neural Network Theory - Lenze, Burkhard (CUBO, A Mathematical Journal, 2001)
In the following paper, we present a brief and easily accessible general survey of the theory of neural networks under special emphasis on the róle of pure and applied mathematics in this interesting field of research.